2018
DOI: 10.29333/ejmste/92019
|View full text |Cite
|
Sign up to set email alerts
|

Further Investigation into the Quality of Teachers’ Noticing Expertise: A Proposed Framework for Evaluating Teachers’ Models of Students’ Mathematical Thinking

Abstract: Because teachers cannot directly access the processes by which students construct their mathematical knowledge, Teacher Noticing, an activity that involves observing students' work, interpreting students' mathematical thinking about a task based on their remarks or actions, and responding to their thinking, is important to grasp students' mathematical understanding. A possible way for teachers to develop noticing expertise is to engage in a situation focused on student thinking such as clinical interviews. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
0
16
0
1
Order By: Relevance
“…however, there is a general consensus that it influences the quality of mathematics instruction (Jacobs et al 2010;Lee 2018). Part of the findings of the study have shown that tutors accurately identified mathematical concepts that were challenging to the students -the assumption here is that the tutor noticing that did take place is evidence-driven.…”
Section: Resultsmentioning
confidence: 71%
“…however, there is a general consensus that it influences the quality of mathematics instruction (Jacobs et al 2010;Lee 2018). Part of the findings of the study have shown that tutors accurately identified mathematical concepts that were challenging to the students -the assumption here is that the tutor noticing that did take place is evidence-driven.…”
Section: Resultsmentioning
confidence: 71%
“…The development of mathematical thinking presupposes a problematic approach to education, which determines the importance of the teacher's work in overcoming fear among students for mathematical research activities (Fouze & Amit, 2018;Lee' 2018;Ramdani, Syamsuddin, & Sirajuddin, 2019;Tambunan, 7 / 20 2019). The authors also believe that it is necessary to take into account students' previous experience in the study of new methods of solution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Understanding teacher learning as "change in discourse over time" (Wilson, Sztajn, Edgington, Webb, & Myers, 2017;p. 570), in particular changes in prospective teachers' discourse on mathematics teaching, can be interpreted as an indicator of enhanced noticing (Ivars, Fernández, Llinares & Choy, 2018). For example, showed that the use of a hypothetical learning trajectory of the part-whole meaning of fractions as a framework to interpret students' mathematical thinking helped prospective teachers improve their mathematical discourse in two ways: firstly, progressing from elaborating a less detailed discourse (in which they did not give evidence or they added unnecessary information from students' answers) to entering a more detailed discourse; and secondly, considering students' answers as examples of more general categories.…”
Section: Developing Prospective Mathematics Teachers' Professional Nomentioning
confidence: 99%